O conteúdo intelectual do lazer no processo do aprender a envelhecer - Campagna, Jossett [UNESP]; Schwartz, Gisele Maria [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2010)
This qualitative study aimed to investigate the resonances of the intellectual content of leisure for older adults. A mixed questionnaire containing ten questions was applied to a sample of fifty older adults people of both genders. Data were descriptively analyzed by thematic content analysis technique and showed that such experiences encourage reflection and the exercise of citizenship. Among the intellectual contents to qualitatively fulfill free time availability were elected by the sample: watching news on TV (70%), videos on health and aging (55%), reading newspapers, magazines and books (54%), playing strategic games (35%) and visiting museums (8%). It can be concluded that the experiences sharpen the critical and intellectual creativity and subsidize better understanding of aging, involving the construction of knowledge and expanding the opportunities of learning to learn, to be, and to live.

Este estudo qualitativo objetivou investigar as ressonâncias das vivências do conteúdo intelectual do lazer para idosos. Na pesquisa de campo utilizou-se como instrumento questionário misto contendo dez questões, aplicado a uma amostra de cinqüenta idosos de ambos os sexos. Os dados foram analisados descritivamente, pela Técnica de Análise de Conteúdo Temático e evidenciaram que tais vivências estimulam a reflexão e o exercício da cidadania. Entre os principais conteúdos intelectuais para o preenchimento qualitativo do tempo disponível foram eleitos pela amostra: assistir noticiários na TV (70%), vídeos sobre saúde e envelhecimento (55%), leitura de jornais, revistas, livros (54%), jogos estratégicos (35%) e visitas a museus (8%). Concluiu que as vivências intelectuais aguçam a crítica e a criatividade e subsidiam melhor compreensão sobre envelhecimento, mobilizando a construção do conhecimento e ampliando as oportunidades do aprender a aprender, a ser, a fazer e a conviver.
The intellectual leisure content in learning the process of aging
Keywords: Leisure; Older Adults; Learning